DEVELOPING ANDROID–BASED EDUTRI (E-MODULE TRIGONOMETRY) FOR GRADE X STUDENTS - Livia Nanda Yantie; Novisita Ratu (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research and development aimed to develop electronic learning media for teaching trigonometry. The media developed was EDUTRI, an acronym for E module trigonometry. This research was conducted on students at class XI IPA 1 and XI IPA 2 of SMA Kristen Satya Wacana, connsiting of 34 students as research subjects. The research utilized R&D with the ADDIE development model. This model consists of 5 stages: analysis, design, develop, implement, and evaluate (evaluation). The validity of the product was examined by the experts’ judgement while the practicality of the e-module media was examined through limited trials with a questionnaire. Then, the product effectiveness was obtained through a one-class trial with a pretest and posttest design. Then, the results were tested by Paired Samples T Test. The final result of this research was an android – based e module media for grade x students. Based on the results from media experts and material experts, android- based learning media was valid with an average score of 98.33%. In addition, the results of questionnaire from teachers and students found the the media was practical with a score of 98.33%. Finally, the results of the Paired Samples T Test Pretest Postest confirmed that Edutri learning media was effective to be used for learning trigonometry, with an average score of 82.4%.